Chemical Composition and Bioactivities of Eugenia caryophyllata Thunb Essential Oil - Fatiha Abdellah (Recent Developments in Chemistry and Biochemistry Research Vol. 4, 2024)
In the present study, the antibacterial activity and antioxidant properties of Eugenia caryophyllata essential oil and its protective effect against lipid peroxidation were investigated. Gas chromatography/mass spectrophotometrical analyses were used to determine the chemical composition of the studied essential oil. The antibacterial activity of E.caryophyllata essential oil was evaluated by using disc diffusion method and agar incorporation method to determine the minimum inhibitory concentration (MIC) of the tested essential oil against four pathogenic bacteria: Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 33862, Bacillus cereus ATCC 11778. The antioxidant activity was evaluated by using tree different tests, DPPH radical scavenging, hydrogen peroxide scavenging assays and ferric reducing antioxidant power (FRAP) assay. Our finding indicated that E. caryophyllata essential oil has shown a strong antibacterial effect against all the tested bacterial strains with inhibition zone diameters varied from 17.5 to 20.5 mm and minimal inhibition concentration (MIC) ranging between 0.8 \(μ\)L / mL and 4.4 \(μ\)L / mL. Gram-positive bacteria, B. cereus and S. aureus are the most sensitive species with a MIC value of 0.8 \(μ\)L / mL, however P. aeruginosa is the most resistant species to the inhibitory effect of the studied essential oil with a MIC value of 4.4 \(μ\)L / mL. The result of the antioxidant effect demonstrated that E. caryophyllata essential oil exhibited a powerful antioxidant activity higher than that of standard antioxidants: gallic acid, vitamin C and BHT. The tested essential oil showed a protective effect against lipid peroxidation better than that of the standard antioxidants: gallic acid and vitamin C, confirmed by a significant decrease in malonic dialdehyde (MDA) levels. These results suggest that the essential oil of E. caryophyllata may be alternative natural source medicine to prevent and treat many diseases caused by pathogenic bacteria and oxidative stress.